2017
DOI: 10.1016/j.canep.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of major life events on breast-cancer-specific mortality: A case fatality study on 8000 breast cancer patients

Abstract: Some major life events regarding close personal relationships may play a role in BC-specific mortality, with certain negative life events increasing BC mortality and positive events decreasing it. The observed favorable associations between positive developments in romantic relationships and hobbies and BC mortality are likely to reflect the importance of social interaction and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…However, our results were in line with studies suggesting that familial confounding may affect the associations between life events and DP due to MSD (Harkonmäki et al 2008;Narusyte et al 2011;Kendler and Baker 2007). Additionally, although several confounding factors including sociodemographic and health may play a role too, previous research support our finding that life event "positive change in life" may decrease the risk of DP due to MSD (Peled et al 2008;Heikkinen et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our results were in line with studies suggesting that familial confounding may affect the associations between life events and DP due to MSD (Harkonmäki et al 2008;Narusyte et al 2011;Kendler and Baker 2007). Additionally, although several confounding factors including sociodemographic and health may play a role too, previous research support our finding that life event "positive change in life" may decrease the risk of DP due to MSD (Peled et al 2008;Heikkinen et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This dilution may reflect that life circumstances and other changes in life may play a role. For example, in previous studies, happiness and positive life events have been shown to decrease risk of breast cancer (Peled et al 2008) and breast cancer mortality (Heikkinen et al 2017). Although cancer is a very different disease than chronic musculoskeletal disorder, these findings together suggest that perceived positive change in life may be an indicator of a factor or factors of beneficial for future health.…”
Section: Discussionmentioning
confidence: 90%
“…Aunque un análisis sobre esta cuestión sobrepasa los objetivos y límites del presente estudio, los sucesos vitales se han asociado a la salud física en general (Holmes y David, 1989;Sandín, 1989Sandín, , 1993Sandín, , 2008, la sintomatología somática (Sandín, Chorot, Santed, y Valiente, 2002), y la mayor parte de las perturbaciones y enfermedades físicas, incluidas las enfermedades cardiovasculares (Bernston, Patel, y Steward, 2017;Chorot y Sandín, 1994;Sandín, Chorot, Santed, y Jiménez, 2009), el cán-cer (Chorot y Sandín, 1994;Heikkinen et al, 2017;, los trastornos gastrointestinales (Tobón, Sandín, y Vinaccia, 2006;Tobón, Vinaccia, y Sandín, 2003), la diabetes y en general las enfermedades autoinmunes y la resistencia a la enfermedad (Holmes y David, 1989;Porcelli et al, 2016;.…”
Section: Introductionunclassified
“…Daily life includes participation in leisure activities, which may mitigate disease-induced stress and reduce feelings of isolation and loneliness [9]. Positively experienced developments in hobbies after diagnosis is shown to reduce deaths from breast cancer [10]. Patients with hobbies lived longer than those without, with an increased number of hobbies reducing the risk of death and curability depending on treatment [9].…”
Section: Introductionmentioning
confidence: 99%